The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1089/vbz.2009.0240
|View full text |Cite
|
Sign up to set email alerts
|

Bird Migration and Risk for H5N1 Transmission into Qinghai Lake, China

Abstract: The highly pathogenic avian influenza H5N1 virus still cause devastating effects to humans, agricultural poultry flocks, and wild birds. Wild birds are also detected to carry H5N1 over long distances and are able to introduce it into new areas during migration. In this article, our objective is to provide lists of bird species potentially involved in the introduction of highly pathogenic avian influenza H5N1 in Qinghai Lake, which is an important breeding and stopover site for aquatic birds along the Central A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Three major Asian migratory bird flyways, the Central Asian, East Asian-Australasian and West Pacific flyways have major stop-over sites in China [3, 4]. Qinghai Lake in Northwest China is one of the most important breeding and stopover sites for migratory birds along the Central Asian Flyway [5]. In 2005 an outbreak of H5N1 in wild birds occurred in Qinghai Lake, and the viruses carried by wild bird migration from Qinghai Lake contributed to the global H5N1 prevalence and to the increase in human H5N1 influenza virus infections [610].…”
Section: Introductionmentioning
confidence: 99%
“…Three major Asian migratory bird flyways, the Central Asian, East Asian-Australasian and West Pacific flyways have major stop-over sites in China [3, 4]. Qinghai Lake in Northwest China is one of the most important breeding and stopover sites for migratory birds along the Central Asian Flyway [5]. In 2005 an outbreak of H5N1 in wild birds occurred in Qinghai Lake, and the viruses carried by wild bird migration from Qinghai Lake contributed to the global H5N1 prevalence and to the increase in human H5N1 influenza virus infections [610].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the lack of detection of the viruses in the birds of present study may be associated with the captured species, which were mostly resident species with terrestrial habits. Cui et al (2011) stated that only aquatic birds of the orders Charadriiformes and Anseriformes are natural hosts of Influenza virus, and in our study, these two orders of aquatic birds accounted for only 18% of the total sample.…”
Section: Discussionmentioning
confidence: 47%
“…The cause of the 2004 outbreak of highly pathogenic avian influenza (HPAI) virus, subtype H7N3, in British Columbia, Canada, was unknown; however, it has been shown that migratory birds can play an important role in the dispersal of influenza A, avian viruses (Webster et al, 1992;Keawcharoen et al, 2008;Cui et al, 2011;Prosser et al, 2011). A similar outbreak of HPAI, subtype H5N1, among village poultry farms in Romania, was associated with exposure to wild migratory waterfowl in the area (Ward et al, 2009).…”
Section: Agentmentioning
confidence: 99%
“…Some disease-causing microorganisms can survive within an avian host for an extended period of time; for example, mallard ducks (Anas platyrhynchos) experimentally-infected with Newcastle Disease virus showed persistent infection and viral shedding for more than two months following exposure (Vickers and Hanson, 1982). Consequently, infected birds might carry micro-organisms during migration (Rappole et al, 2000;Hess and Paré, 2004;Owen et al, 2006;Cui et al, 2011;Prosser et al, 2011). Although migratory birds have the capacity to carry several different poultry diseases (Table 1), this paper will focus on diseases spread by waterfowl, with an emphasis on influenza A, avian virus, to illustrate the potential role that birds play in disease dispersal.…”
Section: Migration and Disease Dispersalmentioning
confidence: 99%